AN ANALYSIS OF FIGURATIVE LANGUAGE ON INSIDE OUT 2 MOVIE - Hapisoh Lubis; Sri Wahyuni Hasibuan; Apriyanti Hasibuan (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This research aimed to analyze the figurative language used in the animation movie Inside Out 2. The objectives were to identify the types and functions of figurative language used by the emotion characters in the movie. The study used a descriptive qualitative method, with data collected from the movie script and dialogues spoken by characters such as Joy, Sadness, Anger, Fear, Disgust, Anxiety, Ennui, Envy, and Embarrassment. Based on Abrams’ theory, the researcher found 10 types of figurative language, including 1 metaphor, 2 similes, 13 hyperboles, 3 personifications, 2 synecdoches, 3 onomatopoeias, 1 allusion, 3 symbolisms, 4 metonymies, and 10 ironies. Furthermore, the functions were analyzed using Perrine’s theory, which includes 11 imaginative enjoyment, 3 detailed imagery, 17 emotional depth, and 11 conveying meaning in few words. The study concluded that figurative language in Inside Out 2 played an important role in expressing emotions, supporting the movie’s theme about growing up and emotional development.Keywords: Figurative language, Inside Out 2, emotional expression